Where do phonological features come from? : cognitive, physical and developmental bases of distinctive speech categories - Clements, George N.; Ridouane, Rachid (Language faculty and beyond ;, 2011)
This volume offers a timely reconsideration of the function, content, and origin of phonological features, in a set of papers that is theoretically diverse yet thematically strongly coherent. Most of the papers were originally presented at the International Conference "Where Do Features Come From?" held at the Sorbonne University, Paris, October 4-5, 2007. Several invited papers are included as well. The articles discuss issues concerning the mental status of distinctive features, their role in speech production and perception, the relation they bear to measurable physical properties in the ar.